Associations between driving under the influence of alcohol or drugs, speeding and seatbelt use among fatally injured car drivers in Norway. (May 2015) - Bogstrand, Stig Tore; Larsson, Magnus; Holtan, Anders; Staff, Trine; Vindenes, Vigdis; Gjerde, Hallvard
Highlights: We studied car and van drivers killed in road traffic crashes. Alcohol or drugs were found in blood samples from about 40% of the drivers. Among impaired drivers, 64.6% had been unbelted and 71.7% speeding. Alcohol and amphetamines were significantly associated with no seatbelt and speeding. Abstract: Since 2005, all fatal road traffic crashes in Norway have been analyzed in-depth by multidisciplinary investigation teams organized by the Norwegian Public Roads Administration (NPRA). During the period 2005–2010, 608 drivers of cars or vans were killed in road traffic crashes. Blood samples were collected from 372 (61%) of the drivers and analyzed for alcohol and a large number of psychoactive drugs at the Norwegian Institute of Public Health (NIPH). After coupling the analytical results with the NPRA crash database, 369 drivers with a fatal outcome were identified and included. Alcohol or drug concentrations in blood above the legal limits were found in 39.8% of the drivers who were investigated for alcohol or drug impairment; 33.9% had blood alcohol concentrations above 0.5 g/L or concentrations of drugs above the equivalent Norwegian legal impairment limits or concentrations of amphetamines above 200 μg/L. Among drivers with a fatal outcome who had been impaired by alcohol or drugs, 64.6% were unbelted and 71.7% were speeding when the crash occurred; whereas 24.2% and 33.2% of the sober drivers were unbelted or speeding, respectively. Statistically significant associations were found between impairment by alcohol or amphetamines and driving unbelted or speeding. Excessive speeding is one of the main reasons for road traffic crashes and together with being unbelted the main reasons for a fatal outcome. This behavior might in many cases be due to increased risk-taking or negligence of safety measures as a result of alcohol or drug use.